PENGARUH BASIS SALEP TERHADAP SIFAT FISIK SEDIAAN SALEP EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) - Wijayanti, Rina; Syarifah, Muslihatus; Goenarwo, Edijanti (Media Farmasi Indonesia, 2014)
ABSTRACT Roselle calyx contains active compounds such flavonoids, tannins, and saponin which can inhibit the growth of S. Aureus bacteria which cause skin infections. Semi-solid preparations suitable for the treatment of skin infections are ointments. The purpose of this study to determine the physical properties of an ointment base ointment preparations Roselle calyx extract (Hibiscus sabdariffa). Experimental research use the ointment samples with 4 kinds of bases (hydrocarbons, absorption, water washed, and dissolved water), with effective substance Roselle calyx extract 1%. Ointment that is produced by physically tested covers : organoleptis, homogeneity, adhesive power, dispersive power, and pH at day 1, 7, 14, 21, and 28. The results showed that in the organoleptic evaluation, and homogeneity, there are no changes in the results during conservation. Ointment base affect adhesion Roselle calyx extract on day 1, 7, 14, and 28; the dispersive power at day 1, 7, 14, 28, but not on day 2; the pH at day 1, 7, and 14, but not on day 21, and 28. The conclusion showed ointment base effect on the physical properties of extract ointment preparations Roselle calyx : adhesion, dispersive power, and pH. But it does not affect the organoleptic and homogeneity. Effective ointment base hydrocarbon base and absorption.